Lender of Last Resort and Global Liquidity - Obstfeld, Maurice (World Bank, 2012)
One important lesson of the crisis is the need to take a systemic view of measures aimed at financial stability. Measures that enhance the stability of a single institution could be inimical to the stability of the financial system as a whole.